EFFECT OF BROILER DROPPINGS ON INDIAN MAJOR CARPS: GROWTH PERFORMANCE AND NITROGEN INCORPORATION. - B. Ahmed; M. Ashraf; M. Naeem; A. Zafar; M. Javed (Journal of Animal and Plant Sciences, 2011)
The effect of poultry droppings on growth of Indian major carps fingerlings was studied. Treatment group 1 (T1) received 0.10% N while 2 (T2) 0.16% N containing manure. The control group did not receive any external input during the whole experimental period. Each treatment group including control had two replicates. Sixty four individuals were stocked in each pond at stocking ratio of Catla catla 25%, Labeo rohita 60% and Cirrhinus mrigala 15% and stocking density was 60 g m-3. A random sample of 7 fishes was weighed and measured for initial weight assessment. Studies were continued for 12 months. At the end of experiment all the fish were harvested, weighed and measured. Significant growth increments were observed in fish reared in manured ponds but negligible growth in control ponds. More nitrogen was incorporated in fish raised on 0.10% N (T1) group than 0.16% N(T2) group. Hence 93% of growth increment can be attributed to nitrates in former and 84% to phosphates in the later group. Performance of the control group remained very poor during the whole study period in both the parameters tested. Therefore, it can be suggested that broiler droppings are appropriate manures to a certain level beyond which it might deteriorate the water quality (pH, dissolved oxygen, total alkalinity and hardness) inflicting a negative impact on fish growth.
Keywords: Broiler droppings; Nitrogen; phosphorus; Indian major carps.